Shear joints and its relations with subsurface structures in Batu Melintang, Jeli, Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Shear joint is the common rock deformation structures formed in Batu Melintang, Jeli due to its location within Bentong-Raub Suture zone. The structural analysis of shear joint can give information about the direction of maximum and minimum stress exerted on a rock while undergoing deformation as the effect of stress fields in the study area. The subsurface structural analysis is done by using the geophysical resistivity method. It displays the subsurface structure in the area for confirmation of the structure found on the surface whether it is highly fractured, moderately fractured or low fractured. The research area was divided into six grids for systematic field measurement. The shear joints orientation were taken while conducting geological mapping and recorded using rose diagram analysis; while the geophysical resistivity method was carried out with a varied length of survey lines set at 200/100m and 1.25/2.5/5m electrode spacing. The subsurface depth of penetration for each survey line is varied, ranging from 0m to 50m. The data is processed in RES2DINV software to obtain the pseudosection profile of the subsurface. The study area principal stress was identified; the maximum stress force ?1 was directed in NW-SE in direction of S107°E and N287°W, while minimum stress ?3 was directed in NE-SW in direction of N17°E and S197°W. The pseudosection subsurface image also displayed a correlation between surface shear joint structures and subsurface structures. The subsurface investigation; according to the pseudosection found that the study area consists of highly fractured structure displayed as several weak zones and fractures of bedrock.
Keywords: shear; joint, stress; subsurface; structure; Jeli